2010
DOI: 10.1007/s00221-010-2470-5
|View full text |Cite
|
Sign up to set email alerts
|

Premovement brain activity in a bimanual load-lifting task

Abstract: Even the simplest volitional movements must be precisely coordinated with anticipatory postural adjustments. Little is currently known about the neural networks that coordinate these adjustments in healthy adults. We measured brain activity prior to movement during a bimanual load-lifting task, designed to elicit anticipatory adjustments in a restricted and well-defined set of musculature in the arm. Electroencephalography and magnetoencephalography brain measurements were obtained from eleven participants whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 84 publications
4
25
0
Order By: Relevance
“…In a recent MEG study of BMLL in healthy adults, Ng et al (2011) reported findings that complement Viallet et al's model. It was noted that, during voluntary unloading, pre-movement brain activity was associated with event-related desynchronization (ERD) of beta-frequency (13-30 Hz) oscillations in the basal ganglia and SMA contralateral to the load-bearing arm.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…In a recent MEG study of BMLL in healthy adults, Ng et al (2011) reported findings that complement Viallet et al's model. It was noted that, during voluntary unloading, pre-movement brain activity was associated with event-related desynchronization (ERD) of beta-frequency (13-30 Hz) oscillations in the basal ganglia and SMA contralateral to the load-bearing arm.…”
Section: Introductionmentioning
confidence: 54%
“…Ng et al, 2011). Visual instructions were presented using E-Prime version 1.0 (Psychology Software Tools, Inc, Pittsburgh, US) and were projected via a mirror onto a screen, which was directly in the participant's line of sight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, EEG does not provide high spatial resolution or clear insight into subcortical functions. Only recently, has an upper-limb load-lifting task been modified for recording by magnetoencephalography in order to gain insight into global cerebral function associated with posture-limb movement coordination (Ng et al, 2011, Ng et al, 2013). A task that requires coordination among the lower limbs and trunk, however, may provide additional insight into postural disorders affecting mobility and balance.…”
Section: Introductionmentioning
confidence: 99%
“…Models of brain lesions (see Massion et al, 1999 for a review), EEG (Martineau et al, 2004), magnetoencephalography (Ng et al, 2011) and fMRI (Schmitz et al, 2005) recordings during the bimanual load-lifting task have shown the involvement of the sensorimotor cortex, the supplementary motor area (SMA), and the basal ganglia within the hemisphere contralateral to the postural arm in the production of APAs. As an alteration of the postural performance was found in patients with a lesion of the primary motor cortex (M1) contralateral to the postural arm only, the specificity of the role of each M1 has been questioned (Viallet et al, 1992).…”
Section: Introductionmentioning
confidence: 99%